Circulating Heat Shock Proteins in Women With a History of Recurrent Vulvovaginitis - P. C. Giraldo; A. D. Ribeiro-Filho; J. A. Simões; A. Neuer; S. B. N. Feitosa; S. S. Witkin (Hindawi Limited, 1999)
Objective: Predisposing factors influencing recurrences of bacterial vaginosis (BV) or vaginitis from Candida remain unidentified for most women. As a component of studies to determine host susceptibility factors to genital tractiiafeetions in women, we measured expression of the 60-kDa and 70-kDa heat shock proteins (hsp60 and hsp70, respectively) in the circulation of women with or without a history of recurrent BV or candidal vaginitis and with or without a current lower genital tract infection. Heat shock protein expression is associated with a down-regulation of proinflammatory immune responses that would inhibit microbial infection.